International Workshop on Computational Intelligence for Multimedia Understanding (IWCIM) 2018
DOI: 10.3390/proceedings2020093
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Representation Based Inpainting for the Restoration of Document Images Affected by Bleed-Through

Abstract: Abstract:Bleed-through is a commonly encountered degradation in ancient printed documents and manuscripts, which severely impair their readability. Digital image restoration techniques can be effective to remove or significantly reduce this degradation. In bleed-through document image restoration the main issue is to identify the bleed-through pixels and replace them with appropriate values, in accordance to their surroundings. In this paper, we propose a two stage method, where a pair of properly registered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This is a well-studied problem with a long line of work. To solve this problem various methods were suggested that include thresholding, partial differential equations (PDE) applica-tion [18,27], sparse representation [15], deep neural networks [16] and optical density models [38], Markov Random Fields (MRF) [37], etc. Sometimes a byproduct of this process is a restored text image from the opposite side that can be considered from the perspective of a palimpsest as an under-text.…”
Section: Bleed-through Removal Modelsmentioning
confidence: 99%
“…This is a well-studied problem with a long line of work. To solve this problem various methods were suggested that include thresholding, partial differential equations (PDE) applica-tion [18,27], sparse representation [15], deep neural networks [16] and optical density models [38], Markov Random Fields (MRF) [37], etc. Sometimes a byproduct of this process is a restored text image from the opposite side that can be considered from the perspective of a palimpsest as an under-text.…”
Section: Bleed-through Removal Modelsmentioning
confidence: 99%
“…Current research on decomposing images with overcomplete dictionaries (i.e. more atoms than the dimension of image) has applications that benefit from sparsity of representation, such as image denoising [27,28], single image super-resolution reconstruction [29,30], image inpainting [31,32], and image compression [33]. A review of sparse representation in dictionary learning and image fusion (by using multiple sensors) was carried out by Zhang et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…[1]These factors may effect on scientific and important cultural material. So to maintain these physical and ancient culture materials some of algorithms and ways are used to improve the quality and remove the clutter by using lots of filters on those materials [2].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%